History of the United Netherlands - Vol. 3 from the death of William the Silent to the synod of Dort : with a full view of the English-Dutch struggle against Spain, and of the origin and destruction of the Spanish Armada - Motley, John Lothrop (Harper & Brothers New York, 1888)
This is a pre-1923 historical reproduction that was curated for quality. Quality assurance was conducted on each of these books in an attempt to remove books with imperfections introduced by the digitization process. Though we have made best efforts - the books may have occasional errors that do not impede the reading experience. We believe this work is culturally important and have elected to bring the book back into print as part of our continuing commitment to the preservation of printed works worldwide
Effect of the Assassination of Henry III -- Struggle of the United Provinces against Philip of Spain -- Philip's scheme of aggrandizement -- Prince Maurice -- War in Brittany and Normandy -- Return of Prince Maurice to the siege of Steenwyk -- Negotiations between Queen Elizabeth and the States -- Influence of the rule and character of Philip II -- Effect of the death of Farnese upon Philip's Schemes -- Prince Maurice lays siege to Gertruydenberg -- Formal declaration of war against Spain -- Archduke -- Struggle of the Netherlands against Spain -- Mission of the States to Henry to prevent the consummation of peace with Spain --Negotiations between France and Spain -- Commercial prospects of Holland -- Military Operations in the Netherlands
maps
44778
Keywords: 1568-1648 -- Netherlands; History -- Eighty Years' War -- 1568-1648.